The Influence of Marketing Costs and Production Costs on Net Profit of Food and Beverage Subsector Manufacturing Companies Listed on The Indonesian Stock Exchange 2020-2023 - Irmawati, Irmawati; Mazidah, Nurul; Hidayatin, Dina Alafi (Universitas Trunojoyo Madura, 2024)
Net profit is one of the leading indicators in investment decision-making. Companies that have a high net profit value are believed to provide prosperity for investors. A company's net profit is obtained from revenue minus costs. The most significant cost components in the food and beverage sector industry profit and loss report are marketing costs and production costs. Thus, these two costs need to be managed well in order to support maximum net profit. This research aims to find out how marketing costs and production costs influence increasing profits in Food and beverage subsector Manufacturing Companies Listed on the Indonesia Stock Exchange. This research used 64 data samples. The results of this research analysis state that marketing costs can have a positive influence on the company's net profit. Likewise, production costs have been proven to have a positive influence on the company's net profit. It is hoped that the results of this research can provide consideration for decision-makers, such as managers and investors, that marketing costs and production costs that can be managed well can contribute to increasing the company's net profit